Techniques Using Artificial Intelligence to Solve Stock Market Forecast, Sales Estimating and Market Division Issues - SANGEETHA, DR. M.; PRIYA, DR. R. MANJU; ELIAS, JIJISH; MAMGAIN, DR. PRADEEP; WASSAN, SOBIA; GULATI, DR. KAMAL (The journal of contemporary issues in business and government, 2021)
This research paper would discuss the use of artificial intelligence (AI) in stock market modelling, sales forecasting, and market segmentation problems, with a focus on convolutional neural networks (CNN) and fuzzy logic. Backpropagation algorithms were used to solve the first two problems, while self-organizing maps were used to solve the third (SOM).